Modelagem para análise de desempenho de fornos micro-ondas no contexto da qualidade de energia elétrica - Almeida, Lucas Rodrigues de (2016)
The electric energy is an indispensable resource in daily life, it is essential since the execution of the simplest everyday tasks in a residence to the diverse needs of a large industry. Due to the complex dynamics of a power system, the problems related to power quality have attracted the interest of researchers, dealers and consumers. In this context, are the investigations related to electrical equipment operation with disturbances of power quality. Experimental testing for performance analysis of such equipment when subjected to non-ideal supply is of fundamental importance. Nevertheless the laboratory tests, the use of computational tools has shown satisfactory results. Given the above, this work aims to contribute to the performance analysis of microwave ovens in the context of power quality. The studies are directed first to the mathematical modeling of a domestic microwave oven and its computational implementation in the program ATP (Alternative Transients Program). Then, its validation is done by comparing the results of computer simulations and laboratory tests, under ideal and non-ideal supply conditions. Finally, a computational modeling is developed in the ATP to represent a high power real industrial microwave oven and its electrical system. Their results are obtained through four case studies that aim to evaluate the impacts that the industrial oven can cause on the supply system power quality.